Dies Irae - Périot, Jean-Gabriel (France : Envie de Tempête Productions, 2005)
A quick paced succession of roads: forest tracks, railroads, highways, village paths, boulevards, walking lanes, and natural passages.
Verzio Film Festival Submission
Keywords: France; Documentary films